Análise do efeito distributivo da precificação de carbono no Brasil - Pereira Júnior, Amaro Olimpio,Maia, Rodrigo,Mendonça, Mário Jorge,Casaca, Paulo Roberto Santos (Instituto de Pesquisa Econômica Aplicada, 2024)
This study aims to analyze the distributional effects of carbon pricing in Brazil. The subject has gained importance with initiatives such as the PMR Brazil Project and RenovaBio, but discussions have been limited to the possible loss of competitiveness of national products. Thus, scenarios built from a computable general equilibrium model were analyzed to assess the impacts of different forms of taxation. The results showed that mechanisms considering taxes without distinction between more or less emitter sectors have little impact on income distribution. In any case, compensation measures are needed to further mitigate the effects on the lower income classes.
10.38116/td3008-port
Keywords: Graue Literatur; income distribution; computable general equilibrium models; carbon pricing